2019
DOI: 10.1016/j.ecss.2019.106327
|View full text |Cite
|
Sign up to set email alerts
|

Understanding marine food web dynamics using fatty acid signatures and stable isotope ratios: Improving contaminant impacts assessments across trophic levels

Abstract: Understanding marine food web dynamics using fatty acid signatures and stable isotope ratios: Improving contaminant impacts assessments across trophic levels. Estuarine, Coastal and Shelf Science, [106327].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 92 publications
2
38
0
Order By: Relevance
“…Consequently, a more comprehensive and alternative analysis of a fish´s diet can be informative and relevant, not only in strengthening and widening the results, but also to discover if there are prey species that were not detectable by visual analysis alone. These methods could be in the form of stable isotope analysis of different fish tissues [76,77], fatty acid profiling [78,79] or genetic analysis of stomach content [80]. In this study, conventional methods were used to evaluate the feeding strategy of the Northeast Atlantic mackerel from stomach content analyses, which showed that mackerel is a specialised feeder upon copepods while in Icelandic waters.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a more comprehensive and alternative analysis of a fish´s diet can be informative and relevant, not only in strengthening and widening the results, but also to discover if there are prey species that were not detectable by visual analysis alone. These methods could be in the form of stable isotope analysis of different fish tissues [76,77], fatty acid profiling [78,79] or genetic analysis of stomach content [80]. In this study, conventional methods were used to evaluate the feeding strategy of the Northeast Atlantic mackerel from stomach content analyses, which showed that mackerel is a specialised feeder upon copepods while in Icelandic waters.…”
Section: Discussionmentioning
confidence: 99%
“…Sample collection and preparation is discussed in detail in Madgett et al, 2019. In summary, 211 samples, including seven fish species (haddock, whiting, hake, plaice, dab, herring and sprat), one shark species (small-spotted catshark) and thirteen invertebrate species (horse mussel, brittle star, hermit crab, edible crab, common starfish, swimming crab, shore crab, European lobster, Nephrops, whelk, sea mouse, squat lobster and veined squid) were collected from nine locations around Scotland between 2015 and 2017 during December and February (Fig.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…Due to factors such as species, location and sample yield, pools were composed of three to six individuals for fish, catshark, common starfish and squid. The remaining invertebrates ranged from twenty to one hundred individuals per pool (Madgett et al, 2019). The length was recorded for all fish and catshark and whole animal weight was recorded for individuals except squat lobsters, swimming crabs, hermit crabs, shore crabs, Nephrops and brittle star where the overall pool was weighed (due to the small size and large quantity of individuals).…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
See 2 more Smart Citations